Data for Formation and impact of nanoscopic oriented phase domains in electrochemical crystalline electrodes - Chen, Wenxiang; Zhan, Xun; Yuan, Renliang; Pidaparthy, Saran; Yong, Adrian Xiao Bin; An, Hyosung; Tang, Zhichu; Yin, Kaijun; Patra, Arghya; Jeong, Heonjae; Zhang, Cheng; Ta, Kim; et al. (University of Illinois at Urbana-Champaign, 2022)
These datasets are for the four-dimensional scanning transmission electron microscopy (4D-STEM) and electron energy loss spectroscopy (EELS) experiments for cathode nanoparticles at different cutoff voltages and in different electrolytes. The raw 4D-STEM experiment datasets were collected by TEM image & analysis software (FEI) and were saved as SER files. The raw 4D-STEM datasets of SER files can be opened and viewed in MATLAB using our analysis software package of imToolBox available at https://github.com/flysteven/imToolBox. The raw EELS datasets were collected by DigitalMicrograph software and were saved as DM4 files. The raw EELS datasets can be opened and viewed in DigitalMicrograph software or using our analysis codes available at https://github.com/chenlabUIUC/OrientedPhaseDomain. All the datasets are from the work "Formation and impact of nanoscopic oriented phase domains in electrochemical crystalline electrodes" (2022).
The 4D-STEM experiment data include four example datasets for cathode nanoparticles collected at different cutoff voltages and in different electrolytes as described below. Each dataset contains a stack of diffraction patterns collected at different probe positions scanned across the cathode nanoparticle.
1. Pristine cathode particle: "Pristine particle 4D-STEM.ser"
2. Cathode particle at the cutoff voltage of 0.09V during discharge at C/10 in the aqueous electrolyte: "Intermediate cutoff0_09V discharge (aqueous) 4D-STEM.ser"
3. Fully discharged cathode particle at C/10 in the aqueous electrolyte: "Fully discharged particle 4D-STEM.ser"
4. Fully discharged cathode particle at C/10 in the dry organic electrolyte: "Fully discharge particle (dry organic electrolyte).ser"
The EELS experiment data includes three example datasets for cathode nanoparticles collected at different cutoff voltages during discharge in the aqueous electrolyte (in "EELS datasets.zip") as described below. Each EELS dataset contains the zero-loss and core-loss EELS spectra collected at different probe positions scanned across the cathode nanoparticle.
1. Pristine cathode particle: "Pristine particle EELS.zip"
2. Cathode particle at the cutoff voltage of 0.09V during discharge at C/10 in the aqueous electrolyte: "intermediate discharge (aqueous) EELS.zip"
3. Fully discharged cathode particle at C/10 in the aqueous electrolyte: "fully discharge (aqueous) EELS.zip"
The details of the software package and codes that can be used to analyze the 4D-STEM datasets and EELS datasets are available at: https://github.com/chenlabUIUC/OrientedPhaseDomain. Once our paper is formally published, we will update the relationship of these datasets with our paper.
Keywords: 4D-STEM; microstructure; phase transformation; strain; cathode; nanoparticle; energy storage